ANALYSIS OF PRINCIPAL'S ACADEMIC SUPERVISION AND TEACHER'S WORK MOTIVATION TOWARD THE PERFORMANCE OF STATE ELEMENTARY SCHOOL TEACHERS IN UNDAAN DISTRICT KUDUS REGENCY - K. Kholid; s. Su'ad; Achmad Hilal Madjdi (Universitas Muria Kudus, 2020)
The objective of this study was to analyze the principal's academic supervision and teacher's work motivation toward the performance state elementary school teachers in Undaan District, Kudus Regency. This research is correlational research with a quantitative approach. The independent variables determined were the principal's academic supervision and teacher's work motivation, while the dependent variable observed was teacher performance. The study was conducted in 33 state elementary schools in Undaan district, Kudus Regency with a sample of 181 respondents. Data collection techniques in this study used interviews, questionnaires, and documentation. Data analysis was performed statistically using descriptive statistical analysis, prerequisite analysis, and final analysis for hypothesis testing. The results of the study found that (1) the principal's academic supervision has a significant effect of 10.10% toward the performance state elementary school teachers in Undaan District, Kudus Regency; (2) the teacher's work motivation has a significant effect of 37.40% toward the performance state elementary school teachers in Undaan District, Kudus Regency; and (3) the principal's academic supervision and teacher's work motivation has a significant effect of 38.40% toward the performance state elementary school teachers in Undaan District, Kudus Regency.